Introduction of Sahar (Tor putitora) in Cage-Cum-Pond Integration System of Mixed-Sex Nile Tilapia (Oreochromis niloticus) - Yadav, RK; Shrestha, MK; Pandit, NP (Our Nature, 2008)
Introduction of sahar in cage-cum-pond integration system of mixed-sex Nile tilapia was evaluated using 15 outdoor cemented ponds of 24 m2 (4.9m × 4.9m) size with 1.25 m water depth placing a cage of 1.2m× 1m × 1m size holding 1 m3 water at the center of each pond at Institute of Agriculture and Animal Science (IAAS), Rampur, Chitwan, for 158 days. The experiment was conducted in a completely randomized design (CRD) with five treatments replicated thrice. The treatments were: large sized Nile tilapia in cage and small sized Nile tilapia in pond (cage-cum-pond system) (T1); cage-cum-pond system with 2 sahar (T2), cage-cum-pond system with 4 sahar (T3), cage-cum-pond system with 8 sahar (T4) and cage-cum-pond system with 16 sahar (T5). Stocking density of caged and pond tilapia was 1 fish/m2 and 2 fish/m2, and size was 78-90 g and 15-16 g respectively. The feed, containing 20% crude protein, was supplied for caged tilapia at the rate of 2% body weight daily. Mean stocking size, harvest size, survival rate, daily weight gain and net fish yield of both caged and pond Nile tilapia were not significantly different among treatments (p > 0.05). Mean harvest weight and daily weight gain of sahar in treatment 2 was significantly higher than other treatments (p < 0.05). NFY of caged tilapia, pond tilapia and combined fish yield were not significantly different among treatments (p > 0.05). Higher numbers of recruits were observed in control and lowest in the treatment 5 suggesting that higher number of sahar in this system effectively controls the tilapia recruits. This experiment showed that addition of sahar in the cage-cum-pond integration system of Nile tilapia effectively controls the number of tilapia recruits and increase NFY. Key words: cage-cum-pond integration, Nile tilapia, Sahar doi:10.3126/on.v5i1.798 Our Nature (2007)5:52-59